769 IMPROVING THE DIAGNOSIS AND MANAGEMENT OF PATIENTS WITH COMMUNITY AND HOSPITAL ACQUIRED PNEUMONIA WITHIN ELDERLY CARE. (8th March 2022) - Hoff, Cv't; Chopra, T; Chatterjee, A
Abstract: Introduction: In 2017 pneumonia was the most cited cause of death in elderly care at our hospital, and in 2019, we were shown to be an outlier in the incidence of hospital acquired pneumonia (HAP). Therefore, accurate diagnosis and management of pneumonia is paramount and an area for improvement in our trust. From 2017–20 we focussed on the care of elderly patients with pneumonia, aiming to improve the diagnosis and subsequent management plans. Methods: Notes were reviewed retrospectively, examining patient notes, EPR data, radiological imaging and pathology results. We had 3 interventions across our project using teaching, posters, screensavers, and involvement of the wider MDT. HAP nursing champions were appointed, and new guidelines were published. Results: Poor diagnostic accuracy of pneumonia was a recurrent problem. In 2017–18, focus to improve diagnosis rested on improved use of baseline investigations. By early 2019, following interventions, 75% of diagnoses were correct for community acquired pneumonia (CAP), despite ongoing poor use of investigations. Conversely, HAP patients had increased investigations but no improvement in diagnosis. Over winter 2019/20, 65% of patients had an inaccurate diagnosis of HAP. The most common reasons for misdiagnosis related to interpretation of chest x-rays and timing of diagnosis. 71% of patients misdiagnosed with HAP received antibiotics which were unlikely to be effective. Conclusion: Improvements were made in the care of patients with both HAP and CAP. Simple interventions such as teaching, screensavers and posters affect decision-making and can improve patient outcomes. Diagnostic accuracy of both CAP and HAP can be a challenge—there were specific areas that were addressed effectively via teaching. To improve sustainability, future success of this project lies with continuous education and training of staff. A steering group will review the whole project and aim to sustain patient outcomes by digital transformation.